"Inverted" CO molecules on NaCl(100): a quantum mechanical study. Issue 13 (27th November 2020) - Sinha, Shreya; Saalfrank, Peter
Abstract : Inverted ("O-down") CO adsorbates on NaCl(100), recently observed experimentally after IR vibrational excitation (Lau et al., Science, 2020, 367, 175–178), are characterized using periodic DFT and a quantum mechanical description of vibrations. Abstract : Somewhat surprisingly, inverted ("O-down") CO adsorbates on NaCl(100) were recently observed experimentally after infrared vibrational excitation (Lau et al., Science, 2020, 367, 175–178). Here we characterize these species using periodic density functional theory and a quantum mechanical description of vibrations. We determine stationary points and minimum energy paths for CO inversion, for low (1/8 and 1/4 monolayers (ML)) and high (1 ML) coverages. Transition state theory is applied to estimate thermal rates for "C-down" to "O-down" isomerization and the reverse process. For the 1/4 ML p(1 × 1) structure, two-dimensional and three-dimensional potential energy surfaces and corresponding anharmonic vibrational eigenstates obtained from the time-independent nuclear Schrödinger equation are presented. We find (i) rather coverage-independent CO inversion energies (of about 0.08 eV or 8 kJ mol −1 per CO) and corresponding classical activation energies for "C-down" to "O-down" isomerization (of about 0.15 eV or 14 kJ mol −1 per CO); (ii) thermal isomerization rates at 22 K which are vanishingly small for the "C-down" to "O-down" isomerization but non-negligible for the back reaction; (iii) several "accidentally degenerate" pairs of eigenstates well below the barrier, each pair describing "C-down" to "O-down" localized states.